Liposomes Loaded With Phosphatidylinositol 5-Phosphate Improve the Antimicrobial Response to Pseudomonas aeruginosa in Impaired Macrophages From Cystic Fibrosis Patients and Limit Airway Inflammatory Response - Poerio, Noemi; De Santis, Federica; Rossi, Alice; Ranucci, Serena; De Fino, Ida; Henriquez, Ana; D’Andrea, Marco M.; Ciciriello, Fabiana; Lucidi, Vincenzina; Nisini, Roberto; Bragonzi, Alessandra; Fraziano, Maurizio (Frontiers in Immunology, 2020)
Despite intensive antimicrobial and anti-inflammatory therapies, Cystic Fibrosis (CF) patients are subjected to chronic infections due to opportunistic pathogens, including multi-drug resistant (MDR) Pseudomonas aeruginosa. Macrophages from CF patients show many evidences of reduced phagocytosis in terms of internalisation capability, phagosome maturation, and intracellular bacterial killing. In this study, we investigated if apoptotic body-like liposomes (ABL) loaded with phosphatidylinositol 5-phosphate (PI5P), known to regulate actin dynamics and vesicular trafficking, could restore phagocytic machinery while limiting inflammatory response in in vitro and in vivo models of MDR P. aeruginosa infection. Our results show that the in vitro treatment with ABL carrying PI5P (ABL/PI5P) enhances bacterial uptake, ROS production, phagosome acidification and intracellular bacterial killing in human monocyte derived macrophages (MDM) with pharmacologically inhibited Cystic Fibrosis Transmembrane Conductance Regulator channel (CFTR), and improve uptake and intracellular killing of MDR P. aeruginosa in CF macrophages with impaired bactericidal activity. Moreover, ABL/PI5P stimulation of CFTR-inhibited MDM infected with MDR P. aeruginosa significantly reduces NF-B activation and the production of TNF-α, IL-1β and IL-6, while increasing IL-10 and TGF-β levels. The therapeutic efficacy of ABL/PI5P given by pulmonary administration was evaluated in a murine model of chronic infection with MDR P. aeruginosa. The treatment with ABL/PI5P significantly reduces pulmonary neutrophil infiltrate and the levels of KC and MCP-2 cytokines in the lung, without affecting pulmonary bacterial load. Altogether, these results show that ABL/PI5P treatment may represent a promising host directed therapeutic approach to improve the impaired phagocytosis and to limit the potentially tissue damaging inflammatory response in CF.